The emergence of scientific tradition in early Islam - Alvi, Faiza Mubin (International Institute of Islamic Thought and Civilization, IIUM, 1999)
All praise be to Allah, the Lord of the Worlds, and peace and blessings be upon Muhammad, the teacher of the book and wisdom. The blind and the seeing are not alike; nor are the depths of Darkness and the Light; nor are the cooling shade and the scorching heat; nor are alike those that are living and those that are dead. God can make any that He wills to hear; but thou canst not make those hear that are (buried) in graves. (Siirah al-Fa,tir, 35: 19-22) Living is thinking and the dead are those that do not reflect. " 'Jim is Islam", remarks a leading orientalist, Franz Rosenthal. A civilization with knowledge as its foundation stone; with knowledge-seeking made obligatory on each of its members (even if it were to China); with immense stress laid on the contemplation and comprehension of the Universe; with the study and reflection upon other nations and civilizations urged and where wisdom is considered to be a gift from the Divine, must be a remarkably dynamic and overpowering civilization, not only in the field of knowledge and sciences but certainly, in every other field and aspect of human life. Indeed, this was so for Islam. Within a century, it had spread across the globe and dominated from Sindh in the East to Spain in the West, which was most of the known world at that time, the American continent had yet to be 'discovered'. Sciences were eminent right from the very beginning in this civilization and were actualized barely a century and a half later. The same Islam, with the same basis and foundations does not, however, find in its members today, the same zeal and vigor for knowledge that had brought about the bloom of sciences in the 7th century. To understand both, how the sciences blossomed in Islam and why they no longer exist, we need to research the foundations of the science and also the development of the sciences specifically in the Islamic civilization. Exploring the philosophical background of Islamic science will shed light not only on the above mentioned issue, but also on the philosophy of science in general as it will approach the subject from a different perspective than it has been so far. Further, it may also give us an insight into why there are no sciences today and how we can revive them. We shall see in this study that Islam was inherently scientific and in fact, sciences could not but have emerged in this civilization. We will note that for the existence of sciences in society, there must be an inherent dynamism within that society, as sciences cannot flourish by being imported from without. We shall, therefore, identify this dynamism as intrinsically present in the epistemological foundation of science. For an exposition of the foundation of science and the emergence of a scientific tradition, we will primarily take Acikgenc's model for the emergence of sciences, as not much work has been done on the epistemological foundations of a science in the same manner as him. By tracing the emergence of a scientific tradition, we will be able to see how and when it emerged in Islam and some of us may be surprised to learn that sciences exist inherently within the Islamic worldview more than any other civilization can claim. Therefore, it is lacking in sciences, not because of Islam, but rather because of its current followers. It will also be realized that borrowing the sciences from the Western or any other civilization cannot be a solution, as sciences must come from within. Insha Allah, we will see that we have the foundation at home within ourselves and we have to revive it on our own. It is hoped that this work will help prompt some action in that direction. Wa Allahu alam bi al-sawab.